Congenital Hypothyroidism and Brain Development: Association With Other Psychiatric Disorders - Uchida, Katsuya; Suzuki, Mao (Frontiers in Neuroscience, 2021)
Thyroid hormones play an important role in brain development, and thyroid hormone insufficiency during the perinatal period results in severe developmental delays. Perinatal thyroid hormone deficiency is clinically known as congenital hypothyroidism, which is caused by dysgenesis of the thyroid gland or low iodine intake. If the disorder is not diagnosed or not treated early, the neuronal architecture is perturbed by thyroid hormone insufficiency, and neuropathological findings, such as abnormal synapse formation, defects in neuronal migration, and impairment of myelination, are observed in the brains of such patients. Furthermore, the expression of psychiatric disorder-related molecules, especially parvalbumin, is significantly decreased by thyroid hormone insufficiency during the perinatal period. Animal experiments using hypothyroidism models display decreased parvalbumin expression and abnormal brain architecture, and these experimental results show reproducibility and stability. These basic studies reinforce the results of epidemiological studies, suggesting the relevance of thyroid dysfunction in psychiatric disorders. In this review, we discuss the disruption of brain function associated with congenital hypothyroidism from the perspective of basic and clinical research.